Nano-structured metal oxide semiconductor material synthesis for anti-bacteria application - Tan, Ooi Kiang. (2008)
The technologies derived from the photocatalytic property of materials are drawing more attention recently as it is possible to complete mineralize the harmful pollutants into harmless compounds with the use of solar energy. However, the most widely used photcatalytic material Titanium Dioxide (TiO2) has a large bandgap of 3.2eV, and thus not efficient under the illumination of normal office fluorescent white light. The focus of this work is in the synthesis and characterization of Sr(Ti1-xFex)O3-δ (STFx), a potentially surperior photocatalyst material by sol-gel and ball-milling technology. The thin films with x values of 0.2 and >0.4 were fabricated through spin coating technique. Thermal property of STFx materials analysis was done by DTA/TGA (Thermogravimetric Analysis/Differential Thermal Analysis). Microstructure properties of STFx films were investigated using X-ray diffraction (XRD), Transmission Electron Microscopy (TEM), optical microscope, Scanning Electron Microscopy (SEM) and Atomic Force Microscope (AFM). The bandgap of the materials were estimated from the results of Transmittance Measurement and Photoluminescence test. Lastly, the photocatalysis properties of the films were accessed by measuring the degradation rate of Methylene Blue under the illumination of fluorescent white light and its water contact angles. Although STFx thin films by sol-gel did show some good properties for photocatalytic reactions in a large surface area, low processing temperature and good uniformity in film, the bandgaps of the materials are still closer the UV side which limits the photocatalytic application of the materials in the visible-light range. However, STFx synthesised by high-energy ball milling have the bandgaps between 2.66-1.8 eV. It has super-efficiency of inactive bacterial (E-Coli). It killed the total bacterial during 45 minutes. This is the first ever report on anti-bacterial for semiconducting material under visible light. P25 have almost no effect on the bacterial under 40 W fluorescent light irradiation.